Ensuring Cybersecurity and Resilience in Solar Smart Grids: Challenges and Solutions - Hossain, Mohammad; Mahjabeen, Farhana (Indonesian Journal Publisher, 2025)
Solar power integration with smart grids has made modern energy systems more efficient and sustainable and increased operational flexibility. The technological benefits of solar smart grids are matched by parallel security issues that need solutions for proper solar smart grid operation. The three main cybersecurity hazards, namely data breaches, denial-of-service attacks, and ransomware, create critical risks that compromise the stability of power grids, consumer privacy, and fundamental infrastructure protection. Solar smart grids need strong resilience against security threats from both cyber and physical sources because their future stability depends on this capability during expanding decentralized energy resource integration. The present work examines major cybersecurity issues that solar smart grids encounter. It investigates methods for solutions through advanced encryption techniques combined with intrusion detection systems and strong communication protocol implementation. To improve security, the paper stresses that distributed control systems and real-time monitoring offer resilience strategies that reduce grid risks. Solar smart grids will maintain their capacity to deliver dependable, sustainable energy through the solutions to these risks.